Transgender dalam Perspektif Hukum Hak Asasi Manusia Internasional dan Hukum Positif di Indonesia - Azahro, Salsa Amalia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Human rights become a hot world issue when their recognition becomes a commitment of every country in the world. The global community is also worried about violations of human rights which frequently occur and are becoming more massive as time goes by. Lesbian, gay, bisexual and transgender issues became increasingly hot on the lips of the public when there was news in the mass media about the ASEAN-wide LGBT meeting being held in Jakarta last July. In this article, the author uses normative juridical research methods. The author will review secondary legal materials, including laws, books, journals and literature related to the research subject, and explain them through descriptive analysis. 20th century, issues surrounding transgender identity began to emerge in various big cities in Indonesia. In the context of performing and martial arts, as well as among male communities in some ethnic groups, same-sex interactions have become common. Human Rights freedoms are supported by the Universal Declaration of Human Rights, namely liberalization of freedom of expression, especially transgender sexual behavior. Transgender issues began to emerge in several large cities in Indonesia at the beginning of the 20th century. Then it began to experience rapid development around the 1960s. Indonesia is a country that respects and upholds human rights in its constitution. The lack of clarity regarding transgender people in both the Universal Declaration of Human Rights and positive law in Indonesia is used as an opportunity for transgender people to fight for their rights